2007
DOI: 10.1038/sj.eye.6702900
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with age-related macular degeneration: results from the VISION study

Abstract: Purpose To assess the impact of treatment with pegaptanib sodium vs usual care on vision-related quality of life (VRQoL) in patients with age-related macular degeneration (AMD). Methods VRQoL was a secondary end point in the trial, a prospective, randomized, doublemasked, multicentre, dose-ranging study. Three doses of pegaptanib (0.3, 1, and 3 mg) were compared with usual care with respect to changes in VRQoL as indicated by the 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ 25), admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…The NEI VFQ-25 composite scores observed in the present study were lower than those reported for patients with PDR, SMD, or Behçet's disease in other studies (8,18,19) . Our patients were younger than those in other studies; therefore, young individuals may experience a greater impact on their QOL with permanent vision loss due to trauma than with other diseases.…”
Section: Discussioncontrasting
confidence: 55%
“…The NEI VFQ-25 composite scores observed in the present study were lower than those reported for patients with PDR, SMD, or Behçet's disease in other studies (8,18,19) . Our patients were younger than those in other studies; therefore, young individuals may experience a greater impact on their QOL with permanent vision loss due to trauma than with other diseases.…”
Section: Discussioncontrasting
confidence: 55%
“…Pharmacotherapy with pegaptanib, ranibizumab, and intravitreal aflibercept have all demonstrated significant improvements in QoL composite score on the NEI VFQ-25, indicating overall improvement in the respondent’s visual health and related functional capacities 13,14,25,26. Other benefits, such as a reduction in the incidence of depression or a decrease in injuries due to falls (a major hazard of vision loss), may also be reflected in improved QoL scores 3,12.…”
Section: Resultsmentioning
confidence: 99%
“…They have been validated by a variety of studies showing they are useful tools in assessing vision-specific quality of life [48]. NEI VFQ-25 is demonstrated to be sensitive to the influence of age related macular degeneration (AMD) [9, 10], glaucomatous field loss [11], cataract [12], Behcet uveitis [13], after penetrating keratoplasty for keratoconus [14], after retinal detachment surgery [15], vitrectomy [16], diabetic retinopathy [17], strabismus [18], multiple sclerosis [19], osteoporotic fractures, and low vision from any cause [20]. The correlations with clinical markers of disease severity provide evidence of clinical validity for the measure.…”
Section: Introductionmentioning
confidence: 99%